1973
DOI: 10.1161/01.cir.48.1s3.iii-56
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Analysis of Preoperative and Postoperative Prognostic Factors in 100 Patients with Combined Aortic and Mitral Valve Replacement

Abstract: From 1963 to 1971, aortic and mitral valves were replaced in 100 patients; 22 died in hospital. Follow-up in survivors is 100%. Catheterization was performed preoperatively in 99 patients and postoperatively in 85% of survivors. The influence of 19 preoperative potential risk factors on hospital mortality, postoperative symptomatic improvement, and long-term survival (assessed by monthly cohort-adjusted survival tables) was determined. Long-term survival was also assessed by comparing average values of the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…[19][20][21] Melvin found that MR+AR was the most common combination of rheumatic valvular lesions. 22 In a study by Essien I O et al, in Nigeria isolated mitral valve involvement was seen in 65.45% isolated aortic valve involvement in 1.8.% and mitral and aortic valve involvement in 33.3% of patients so it matches with present study. 23 In a study by J.N.…”
Section: Discussionsupporting
confidence: 90%
“…[19][20][21] Melvin found that MR+AR was the most common combination of rheumatic valvular lesions. 22 In a study by Essien I O et al, in Nigeria isolated mitral valve involvement was seen in 65.45% isolated aortic valve involvement in 1.8.% and mitral and aortic valve involvement in 33.3% of patients so it matches with present study. 23 In a study by J.N.…”
Section: Discussionsupporting
confidence: 90%
“…Melvin also found that MR+AR, was the most common combination of rheumatic valvular lesion. 54 TS was rheumatic in our study and was almost exclusively seen in association with MR+AR (1.03%). In the necropsy series of Roberts and Virmani.…”
Section: Rv Functionsupporting
confidence: 52%
“…A study of 100 patients with combined aortic and mitral valve replacement discovered that MR + AR was the most common combination of rheumatic valvular diseases. 30 Only 10 patients were reported to have virtually pure AS and AR in a group of patients with mixed aortic and mitral valve disease. 31 …”
Section: Discussionmentioning
confidence: 99%